Konsinyasi/Penitipan Uang Sebagai Bentuk Ganti Rugi Atas Pengalihan Hak Tanah - Stevi Hendi Lawalata; Jenny Kristiana Matuankotta; Novyta Uktolseja (PAMALI: Pattimura Magister Law Review, 2021)
Introduction: Securing land for the building of the Hunimua Ferry Crossing Port in Liang State, Central Maluku Regency, the deliberate mechanism that should be a means of compromise in the form of mutual compensation often does not reach a consensus, hence the way the dispute is resolved through the court's channel. On the other hand, in order for the completion of the assumed oil price to be paid by monetary or monetary services.Purposes of the Research: The study will review payment procedures by conifers and other monetary services for the development of the Hunimua ferry crossing of maluku district as a transference of land rights.Methods of the Research: The study is normatif yuridis, using analytic descriptive research types by using primary, secondary and tertiary source material. The approach used was a statute approach, a conceptual approach and a case approach. The technique for collecting legal materials used literature studies that were then analyzed qualitatively to address the issues discussed.Results of the Research: Payment procedures through consignment / deposit of money conducted by PT.  ASDP Ferry (PERSERO) is in accordance with the provisions of the national land law in terms of the transfer of rights, which has been carried out according to land acquisition procedures through socialization and deliberation with land rights holders, but because the land is still in dispute, it is in accordance with the provisions of Law No.  2 of 2012, PT ASDP Fery Persero made a request for payment through consignment / deposit money.  The consignment / deposit of money by PT ASDP Fery Persero for the construction of the Hunimua Ferry Crossing Port in Liang State, Central Maluku Regency has legal consequences for the transfer of land rights which are transferred from land rights holders to PT ASDP Fery Persero so that the construction activities of the Hunimua Ferry Port expansion can be carried out.